Title Prototype of a Mobile-Based Interactive Application for Tourist Search in Nabire - Prayitno, Gunawan; Bouk, Gatrida (Brilliance: Research of Artificial Intelligence, 2024)
The Nabire area in Papua Indonesia has rich natural tourism potential, including attractive lakes and beaches. However, the low interest of tourists in visiting is caused by a lack of information and promotion about this tourist destination. The lack of efforts to disseminate information and promotions has resulted in low numbers of tourist visits, both domestic and international. This research aims to overcome this problem through the development of an interactive mobile application designed to facilitate access to comprehensive and up-to-date tourist information in Nabire. This research methodology uses a Design Thinking approach which consists of five stages: empathy, determination, ideation, prototype, and test. At the empathy stage, observations and interviews were carried out to understand user needs, which revealed that easily accessible and complete tourism information was still very much needed. The determination stage concluded that the main problem was the lack of accessibility of integrated and up-to-date tourism information. The ideation stage produced several potential solutions, including creating an application that provides complete information about tourist attractions, ticket prices, locations, images and videos. In the prototype stage, the application is designed using Figma to showcase important features and produce an initial model that can be tested. The prototype results include a main page, a short tourist description, a photo gallery, and a tourist video. The testing phase is carried out using the black box method to ensure the application functions operate as expected. Test results show that the application can display dashboard pages, short tourist descriptions, photo galleries and videos well.